No association between incidence of type 1 diabetes and rotavirus vaccination in Swedish children - Rangert, Amanda; Oldin, Carin; Golsäter, Marie; Ludvigsson, Johnny; Åkesson, Karin (Frontiers in Immunology, 2023)
Rotavirus infection is a potential trigger of type 1 diabetes (T1D) and rotavirus vaccination is hypothesized to decrease the incidence of T1D. In Sweden, rotavirus vaccination was introduced in 2014 in two regions and from 2019, nationwide. This study aims to investigate the association between rotavirus vaccination and incidence of T1D in Swedish children and whether rotavirus vaccination is associated with a change in clinical manifestation at diabetes onset.A nationwide register-based study with all Swedish children <15 years of age, diagnosed with T1D 2009-2019 was conducted. 7893 children were retrieved. Nationwide vaccine coverage was collected from Child Health Services. Three vaccine groups were created: I: Vaccination